AN EFFORT TO IMPROVE THE ABILITY OF BASIC TECHNIQUES IN VOLLEYBALL GAMES WITH MAKE A MATCH - Kamadi, La; Nur, Muhammad (ILIN Education Indonesia, 2024)
Classroom Action Research aims to improve physical education learning in performing basic techniques in volleyball games with make a match. In this study, researchers collaborated with other teachers and with the school principal. Researchers were directly involved in the research from the beginning until the research ended. Researchers try to see, observe, feel, live, reflect and evaluate the learning activities that take place. This research used 2 cycles consisting of planning, acting, observing, and reflecting. Data collection techniques to obtain accurate research results, the data that has been collected is analyzed statistically, namely using the mean or average formula. From the results of the study it was found that the average value of cycle I was 66.14 (46.33%) while Cycle II was 91.29 (96.43%) in cycle II experienced a significant increase. Referring to the action hypothesis proposed in this class action research, it can be concluded that there is an increase in the ability of basic techniques in volleyball games with make a match in class XI students of SMA Negeri 2 Sinjai.